Stung - Wiggins, Bethany (New York, NY : Walker & Company, 2013)
When a vaccine to save endangered bees causes their sting to turn children into ferocious killer beasts, the uninfected build a wall to keep the beasts out, but Fiona wakes up on the wrong side of the wall.
Keywords: Survival -- Juvenile fiction; Science fiction